(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: The area of temporomandibular joint (TMJ) surgery has advanced significantly, yet recent years have seen a number of noteworthy failures. Despite the issues, TMJ surgery continues to play a little but crucial part in the treatment of some temporomandibular diseases. An overview of TMJ surgery is provided in this article. It is concluded that the key to a successful conclusion is cautious case selection